Financial Management Training As An Effort To Improve The Reliability Of Preparation Of Financial Statements - Nur Khamisah; Arista Hakiki; Rahma Nida; Hasni Yusrianti; Christian Damar Sagara Sitepu (Faculty of Economics, Universitas Sriwijaya, 2023)
Financial Statement is one of very important element in business, because it is an output that can give information for user as base for taking decision. The problems faced cooperative employees of PT PUSRI Palembang are, they not yet understand about financial management in compile report effective and efficient finance. Financial management need understood for cooperative manager, because its related with the reliability of information in financial statement cooperative . This community service activity aims to provide knowledge and skills regarding financial management in order to increase the reliability of financial statement to the target group, namely the PT PUSRI Palembang employee cooperative. Activity devotion done with method outreach and training . Benefit from activity devotion to employees cooperative PT PUSRI Palembang is expected become useful input for participants activity capable to manage financial in a effective and efficient manner so the cooperative objective can optimally achieved. Besides it, with knowledge management good finances owned by the participants can used as consideration in taking decision related finance nor direction policy business in a manner more broad .